EMPOWERMENT PROGRAM FOR FEMALE WORKERS IN THE COASTAL FISH-PROCESSING INDUSTRY BASED ON ERGONOMICS AND THE ENVIRONMENT: PROGRAM PEMBERDAYAAN PEKERJA WANITA PADA INDUSTRI PENGOLAHAN IKAN PESISIR BERBASIS ERGONOMI DAN LINGKUNGAN - Globila Nurika; Ana Islamiyah Syamila; Cantika Almas Fildzah (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Most fish processing workers perform tasks in non-ergonomic positions, such as bending at an angle greater than 20° and turning their necks, with their legs bent at an angle greater than 60°. In addition, these fish-processing practices do not yet incorporate optimal waste management, thereby affecting workers’ health and contributing to environmental pollution. Objective: This activity aims to empower female workers in the coastal fish-processing industry by applying ergonomic principles and waste-management innovations. Method: The Participatory Rural Appraisal method was used in this activity, utilizing educational media in the form of modules and posters. This program runs for 8 months with 20 female workers. Four stages of activity were implemented: outreach and training, technology implementation, mentoring, and monitoring and evaluation. Pre-test and post-tests, as well as direct observations, were conducted to evaluate the achievement of the activity’s objectives. Results: This activity shows an increase in female workers’ knowledge, with scores rising from 56.2 on the pre-test to 84.5 on the post-test. Observations of the female workers’ skills also indicate that all were able to implement practices to prevent work related fatigue and manage waste. Conclusion: The community service carried out at UD LASKAR AMIS in Puger Kulon, Jember Regency, has enhanced female workers’ knowledge and skills in preventing occupational fatigue and managing waste generated during fish processing.